(untitled) (Central Asian Journal of Medical Sciences, 2023)
Objective: This study aimed to estimate the knowledge of the legal regulation of euthanasia and painless death among terminally ill patients, their caregivers, and attending physicians. Methods: The study was conducted using an analytical survey design and evaluated by a questionnaire of the target sample group. Results: According to the patient’s age group, those under 49 were most likely to support euthanasia at 93.1%, and those over 50 were 73.3%. Furthermore, 87.5% of those who said they had financial problems, 91.7% of those who said they had long queues at the hospital, difficulty in getting medical care, 66.7% of those who said they were bedridden or had a lot of pain, and 100% of those who said they would have mental depression or other problems were in favor of euthanasia. In the physicians, 96.6% of the doctors who participated in the study said they knew about euthanasia, 100% of those who believed that euthanasia was ethical and knew the types of euthanasia, and 95% of those who thought that there were ethical differences in the types of euthanasia, supported euthanasia. Conclusion:Our study demonstrated that caregivers generally support the legalization of euthanasia. 70.8% of those who said that euthanasia could be performed by medical indications, 79.2% of those who said that it could be performed at the request of the patient, 54.2% of those who said that it could be performed at the request of the family of a patient without legal capacity, and 35.4% of those who said that it could be performed at the request of a treating physician tended to support euthanasia.